Assessment of students’ EFL learning outcomes during emergency remote teaching: Teachers’ challenges and practices - Laily, Farida Nur; Suparno, Suparno; Ngadiso, Ngadiso (Universitas Lampung, 2022)
The assessment of students’ learning outcomes during COVID-19 pandemic has become a burnng issue among educators. The extreme diversion from face-to-face learning to emergency remote teaching resulted in the assessment being carried out remotely. This case study research is aimed to investigate how the assessment practices of students’ EFL learning outcomes during emergency remote teaching and to discover the challenges faced by the teachers in assessing students’ EFL learning outcomes. To obtain the data, interviews were conducted with two senior high school teachers. Both teachers are from different regions in Indonesia. From the data analysis, it was revealed some findings that the challenges faced by EFL teachers in assessing students’ learning outcomes are mainly related to the (1) academic dishonesty, followed by (2) deciding the appropriate tools or applications for assessing students’ outcomes and the last is (3) engaging students in the assessment process. Teachers’ creativity is regarded as critical in order to effectively assess students’ EFL learning outcomes.